2018
DOI: 10.1186/s13071-018-2888-3
|View full text |Cite
|
Sign up to set email alerts
|

Wing morphometrics of Aedes (Ochlerotatus) albifasciatus (Macquart, 1838) (Diptera: Culicidae) from different climatic regions of Argentina

Abstract: BackgroundGene flow restrictions between populations of Aedes albifasciatus, the vector of Western equine encephalitis and Dirophilaria immitis, have been described in the central region of Argentina. Genetic and eco-physiological variations usually result in local forms reflecting the climatic regions. Mosquito wings and their different parts have ecological functions in flight and communication. Therefore, wing shape could be considered an aspect of sexual dimorphism, and its eco-physiological responses can … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 60 publications
2
7
0
Order By: Relevance
“…Furthermore, in general terms, this hypothesis seems to support the fact that Calliphoridae have a more static region at the wing base (lm 1, lm 12 to lm 17), the rest of the wing forms a more variable region. Similar results have been obtained in Culicidae, where females showed greater variability of shapes than males at the margen and medium area of the wing (the wings of the females were wider in the anterior-posterior sense, while the males had narrower wings); it is indicating a greater sensitivity to the different rearing temperature conditions in females [65][66].…”
Section: J O U R N a L P R E -P R O O Fsupporting
confidence: 84%
“…Furthermore, in general terms, this hypothesis seems to support the fact that Calliphoridae have a more static region at the wing base (lm 1, lm 12 to lm 17), the rest of the wing forms a more variable region. Similar results have been obtained in Culicidae, where females showed greater variability of shapes than males at the margen and medium area of the wing (the wings of the females were wider in the anterior-posterior sense, while the males had narrower wings); it is indicating a greater sensitivity to the different rearing temperature conditions in females [65][66].…”
Section: J O U R N a L P R E -P R O O Fsupporting
confidence: 84%
“…6) of Uranotaenis sp1 from the Anorana and Maromizaha forests would indicate a conspecific status. Moreover, the use of only females for wing morphometric analysis would reduce the interpretation bias due to the sexual shape dimorphism as described in Aedes albifasciatus (Macquart) (not recorded in Madagascar) (Garzón & Schweigmann 2018). The significant variation in the size of the wing with no difference in wing shape of Uranotaenia sp1 may be due to the fact that wing size variation is associated with environmental affects, while wing shape variation may be explained by chromosomal polymorphism (Ayala et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…A previous study conducted between migrant and non-migrant populations in dragonflies showed important wing shape modifications (Johansson et al, 2009). A previous morphometrics study revealed that thinner wings could be more adaptive for Aedes albifasciatus (Macquart, 1838) (Diptera: Culicidae) populations to avoid disturbance in a windy environment (Garzón & Schweigmann, 2018). Other studies conducted with Ae.…”
Section: Discussionmentioning
confidence: 99%